2022
DOI: 10.1002/cbic.202200231
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids from Streptomyces: Structures, Biosyntheses and Bioactivities

Abstract: Bacteria, especially Streptomyces spp., have emerged as a rich source for natural diterpenoids with diverse structures and broad bioactivities. Here, we review diterpenoids biosynthesized by Streptomyces, with an emphasis on their structures, biosyntheses, and bioactivities. Although diterpenoids from Streptomyces are relatively rare compared to those from plants and fungi, their novel skeletons, biosyntheses and bioactivities present opportunities for discovering new drugs, enzyme mechanisms, and applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…Then, GGPP is converted to a (+) copalyl diphosphate under the catalysis of AtrB. AtrD dephosphorylates the (+) copalyl diphosphate, yielding a labdane-type bicyclic diterpene, labda-8(17),12,14-triene, that is subsequently hydroxylated at C7 by AtrC to form raimonol . AtrE oxidizes raimonol, creating an aldehyde group at C10 to produce labdanmycin A. Labdanmycin A undergoes a reaction akin to aldol condensation under acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, GGPP is converted to a (+) copalyl diphosphate under the catalysis of AtrB. AtrD dephosphorylates the (+) copalyl diphosphate, yielding a labdane-type bicyclic diterpene, labda-8(17),12,14-triene, that is subsequently hydroxylated at C7 by AtrC to form raimonol . AtrE oxidizes raimonol, creating an aldehyde group at C10 to produce labdanmycin A. Labdanmycin A undergoes a reaction akin to aldol condensation under acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Li observed that most diterpenes tapped through genome mining in streptomycetes exhibit novel skeletons, and the activation and exploration of the terpenoid gene clusters within streptomycetes holds the potential for discovery of novel terpenoids. 18 In this study, we identified an atr terpenoid gene cluster from S. atratus Go66. Subsequently, this gene cluster was cloned and heterologously expressed in S. albus J1074, which led to isolation of three new labdane diterpenoids featuring an unprecedented 6/6/5-fused tricyclic skeleton, designated as atralabdans A−C (1−3), and a known compound, labdanmycin A.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The strains S. sanglieri YIM 121209-2 [91], S. anulatus YIM 101882 [92], and Streptomyces sp. RM-14-6 [93] produced new 15-hydroxy-(+)-epi-cubenol (34), 5,11-epoxy-10-cadinanol (35), and isopterocarpolone (41), respectively.…”
Section: Mono-and Sesquiterpenes and Their Derivativesmentioning
confidence: 99%
“…Terpene biosynthesis by actinomycetes is an actual research area discussed in research and review publications. However, the specialized reviews are focused on certain genera of actinomycetes and/or groups of terpene derivatives [ 41 , 42 ], bacterial terpenome [ 43 ], and evolution and ecology of microbial terpenoids [ 44 ]. The present review aims at assessing the biosynthetic potential ( via the patent analysis in particular) of various representatives of Actinomycetes as producers of a wide range of biologically active terpenoids, including hybrid metabolites (meroterpenoids).…”
Section: Introductionmentioning
confidence: 99%